THE PROCESS OF TEACHER’S LESSON PLAN FOR LEARNING ENGLISH THROUGH GOOGLE CLASSROOM IN THE SENIOR HIGH SCHOOL - Arsini, Ni Wayan Widya; Tantra, Dewa Komang; Suprianti, G.A.P (Jurnal Pendidikan Bahasa Inggris undiksha, 2021)
During the pandemic, the education system in Indonesia was prepared and implemented through online learning media. Teachers are still lacking in detail in preparing appropriate learning plans for online learning. It results in learning activities not running optimally. English teachers must develop lesson plans based on standard rules in the curriculum. It is so that learning activities can run optimally. The objectives of this study are the process and difficulties faced by English teachers in preparing English lesson plans during a pandemic situation, where learning is carried out through Google Classroom. This research is a qualitative descriptive study with the subject of research being English teachers. Data was collected through a questionnaire regarding lesson plan simplification, which included learning objectives, materials, activities, media and sources, and assessment. The data obtained were analyzed descriptively and qualitatively. The results showed that the teacher fulfilled all the steps in the five aspects of the one-page lesson plan, which fulfilled the steps provided by the instrument. Meanwhile, in compiling the RPP for learning English through Google Classroom, the teacher found a problem: the learning objectives that included an audience. Research findings indicate that improvements are needed in learning and its implementation through online learning platforms.